Extracellular vesicle-derived long non-coding RNA as circulating biomarkers for endometriosis. Issue 5 (May 2022) - Shan, Shan; Yang, Yeping; Jiang, Jilan; Yang, Bingxin; Yang, Yisai; Sun, Feng; Zhang, Junyu; Lin, Yu; Xu, Hong
Abstract: Research question: Could extracellular vesicle-derived long non-coding RNA (lncRNA) serve as promising circulating biomarkers for endometriosis? Design: To obtain novel diagnostic markers, 85 patients with endometriosis were enrolled as the endometriosis group and 86 unaffected participants as the control group. RNA sequencing was performed to identify extracellular vesicle-derived lncRNA that were differentially expressed between women with endometriosis ( n = 5) and unaffected participants ( n = 6). Messenger RNA and lncRNA sequences of the plasma extracellular vesicles were analysed using Gene Ontology and Kyoto Encyclopedia of Genes and Genomes analyses. lncRNA expression levels were further validated using quantitative reverse transcriptase polymerase chain reaction. Moreover, receiver operating characteristic curve analysis was performed to determine the diagnostic value of candidate lncRNA. Clinical features were correlated to the expression levels of candidate lncRNA. Results: It was found that 210 lncRNA were significantly dysregulated; among these, expression of LINC01569, RP3-399L15.2, FAM138B and CH507-513H4.6 was significantly decreased, whereas expression of RP11-326N17.2, KLHL7-AS1 and MIR548XHG was increased, in the plasma of patients with endometriosis. Combined expression level of RP3-399L15.2 and CH507-513H4.6 was used to distinguish patients with endometriosis from control participants; the results revealed a sensitivity of 80.00% and specificity of 85.45% at the cut-off point, and an area under the ROC curve of 0.9045. The findings demonstrated the potential of these two lncRNA as diagnostic biomarkers for endometriosis. Moreover, CH507-513H4.6 alone may be useful in detecting early-stage endometriosis lesions. Conclusions: The combination of RP3-399L15.2 and CH507-513H4.6 may be a potential candidate for endometriosis biomarkers.